Ribosome-stalk biogenesis is coupled with recruitment of nuclear-export factor to the nascent 60S subunit - Sarkar, Anshuk; Pech, Markus; Thoms, Matthias; Beckmann, Roland; Hurt, Ed (Nature structural & molecular biology, 2016)
The ribosome-assembly factor Mrt4 prevents untimely recruitment of the RNA-export receptor Mex67-Mtr2 to the nascent 60S ribosomal subunit, thereby ensuring appropriately timed nuclear export.
Gesehen am 08.05.2020